(untitled) (Research, Society and Development, 2021)
Low back pain or low back pain is a disorder that can be of traumatic, biomechanical or biopsychosocial origin, affecting both sexes and that can be characterized by the presence of pain of an acute or chronic nature. The study aimed to search the literature for evidence on the performance and effectiveness of hydrotherapy in patients with low back pain. A systematic review study was carried out in the following databases: PEDro, Scielo, PubMed using the descriptors in Spanish, English and Portuguese published in recent years. After careful analysis of the results obtained, 04 articles that contribute to the study were selected. It is noteworthy that the authors show that hydrotherapy is effective in the treatment of pain and improves the quality of life of individuals, it is important to mention the need for more clinical trials in the area to show evidence of hydrotherapy in patients with low back pain.